2018
DOI: 10.4236/cus.2018.61003
|View full text |Cite
|
Sign up to set email alerts
|

Sector-Wise Exploratory Analysis of Household Residential Location Choice in the African Context: Empirical Evidence from Benin City, Nigeria

Abstract: This study explored the residential choice of households based on the discrete choice model. Although, many authors in Africa cities have commented on this choice behavioural process. Notwithstanding, empirical study in this area is still lacking. There is a need to provide understanding on the household choice and decisions that influences the structure of urban landscape. A sector-wise model was formulated and used to estimate the choice behaviour of 1100 households in the area. However, the model shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 68 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…The study suggests that socio-cultural, dwelling and accessibility considerations are significantly more important than the housing attributes related to the neighbourhood. Similarly, the findings of Nkeki and Erimona (2018) reflect on the role of socio-cultural cohesion and accessibility as the most prominent determinants of household choice of residential location in Benin City, Nigeria. This view is supported by Acheampong and Anokye (2013).…”
Section: Factors Influencing Choice Of Residential Locationmentioning
confidence: 77%
See 1 more Smart Citation
“…The study suggests that socio-cultural, dwelling and accessibility considerations are significantly more important than the housing attributes related to the neighbourhood. Similarly, the findings of Nkeki and Erimona (2018) reflect on the role of socio-cultural cohesion and accessibility as the most prominent determinants of household choice of residential location in Benin City, Nigeria. This view is supported by Acheampong and Anokye (2013).…”
Section: Factors Influencing Choice Of Residential Locationmentioning
confidence: 77%
“…Contrastingly, these authors critique the work of Jun and Morrow-Jones (2011) who suggest that the role of neighbourhood characteristics are significantly more important than housing attributes. Nkeki and Erimona (2018) did not take into account the function of dwelling attributes in their study. They considered socio-economic attributes, and like Zondag and Pieters (2005) and Opaluwa and Aribigbola (2015), find the component to be significantly less important.…”
Section: Factors Influencing Choice Of Residential Locationmentioning
confidence: 99%
“…The study suggests that socio-cultural, dwelling and accessibility considerations are significantly more important than the housing attributes related to the neighbourhood. Similarly, the findings of 43 reflected on the role of socio-cultural cohesion and accessibility as the most prominent determinants of household choice of residential location in Benin City, Nigeria.…”
Section: Determinants Of Household Residential Location Choicementioning
confidence: 92%
“…The second part of the analysis is the development of a residential location choice model using multinomial logit regression (MNL). In similar choice scenarios, MNL models have been the most widely used regression models (Kumar and Krishna Rao, 2005;Nkeki and Erimona, 2018;Pandya and Maind, 2017). These models are generally derived from the assumption of utility maximization, which states that the decisionmaker selects the alternative which gives maximum utility.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Zhan (2015) found that the presence of children in households resulted in the consideration of locations with good-quality schools. Gilbert and Gugler (1982), Nkeki and Erimona (2018) and Schirmer et al (2014) found that households tend to cluster within the spatial boundaries defined by their income and ethnicity.…”
Section: Household Characteristicsmentioning
confidence: 99%